Magnesium Zinc Oxide Nanostructure-modified Quartz Crystal Microbalance for Dynamic Monitoring of Antibiotic Effects and Antimicrobial Resistance. (2017) - Reyes, Pavel Ivanoff; Yang, Keyang; Zheng, Andrew; Li, Rui; Li, Guangyuan; Lu, Yicheng; Tsang, Chi Kwan; Zheng, Steven X.F.
Abstract: We demonstrate a magnesium zinc oxide (MZO) nanostructure-modified quartz crystal microbalance (MZOnano -QCM) biosensor to dynamically monitor antimicrobial effects on E. coli and S. cerevisiae. The MZO nanostructures were grown on the top electrode of a standard QCM using metal-organic chemical-vapor deposition (MOCVD). The MZO nanostructures are utilized as the sensing material due to their multifunctionality, biocompatibility, and very large effective sensing surface. The MZO surface-wettability and morphology are controlled, offering high-sensitivity to various biological/biochemical species. The MZOnano -QCM was applied to detect the effects of ampicillin and tetracycline on sensitive and resistant strains of E.coli, as well as effects of amphotericin-B and miconazole on S. cerevisiae through the device's time-dependent frequency shift and motional resistance.